2003
DOI: 10.1097/00005131-200308000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pin Tract Infection With Contemporary External Fixation: How Much of a Problem?

Abstract: Patients with hybrid external fixators had a similar risk of pin tract infection as patients who had unilateral fixators. The infection rate in the ring fixator group was significantly lower than the hybrid external and unilateral fixator groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
132
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(145 citation statements)
references
References 12 publications
4
132
0
1
Order By: Relevance
“…28,29 This led to unwanted motion and the fracture site with resultant loss of reduction, non-union and increased pin-site infection rates. [30][31][32][33][34] Conventional circular external fixation, however, has recently emerged as a viable treatment alternative for bicondylar plateau fractures. 8 These fixators use beam loading through the entire span of the fixator that results in symmetrical loading of the fracture site.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 This led to unwanted motion and the fracture site with resultant loss of reduction, non-union and increased pin-site infection rates. [30][31][32][33][34] Conventional circular external fixation, however, has recently emerged as a viable treatment alternative for bicondylar plateau fractures. 8 These fixators use beam loading through the entire span of the fixator that results in symmetrical loading of the fracture site.…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors that may contribute to pin tract infection include the thickness of the soft tissue mantle between the skin and bone, with anatomical areas with thicker soft tissue envelopes, such as the thigh, associated with higher infection rates [22]. In our study, there were 17 sites with superficial infection, of which 2 sites were in the femur (4.4% of the femoral pin insertion sites) and 15 sites were in the lower leg (4.5% of the lower leg pin insertion sites).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, it was found that pin tract infection rate was 20% and the rate of pin loosing was 15% (9). Rates for pin tract infections were reported to be 11.2% to 63%, by other studies (11)(12)(13)(14). Because of the prevalence of femur and hip fractures, several studies have focused on these fractures (3,4), and its hospital costs (6).…”
Section: Introductionmentioning
confidence: 99%
“…Another study investigated the functional outcomes after hip fractures (2). Few studies also focused on patients under traction and reviewed or investigated the benefits, indications, techniques, and complications of skeletal or skin tractions (8)(9)(10) and pin tract infection rates (13,14). However, only one study was found that focused on the nurses' knowledge and practice concerning care of patient with skin traction in Iraq and reported a poor performance (16).…”
Section: Introductionmentioning
confidence: 99%